BAS/BSCR18 Protection from development of obesity in high-fat diet fed rats is associated with preservation of the anticontractile function of perivascular adipose tissue. Issue 17 (26th August 2010) - Aghamohammadzadeh, R; Greenstein, A S; Park, B H; Porter, E L; Edwards, G; Weston, A H; Heagerty, A M
Abstract : Introduction: In health, perivascular adipose tissue (PVAT) has an anticontractile function on adjacent small arteries. We have recently shown that adipocyte hypoxia and inflammation in obesity attenuates PVAT anticontractile function. In animals, PVAT function has only been examined in genetic models of obesity, which are rare in clinical practice. Methods: 11 Sprague–Dawley rats were fed a high-fat diet (HF; n=11) over 15–18 weeks. Seven control animals received a normal diet. Weight and blood pressure were monitored. The HF rats were split into two groups: (a) diet-induced obese (DIO; n=6): significantly gained weight after a 10-week period, and diet resistant (DR; n=5): weight comparable to control group. Mesenteric arteries were studied using wire myography with construction of cumulative dose responses to noradrenaline, with and without PVAT intact. Results: The weight and systolic blood pressure for DIO were significantly increased compared with the controls (systolic BP: control: 124%±4; DR: 138%±8; DIO: 150%±3 p<0.05). The contractile responses of vessels with intact PVAT were significantly different from vessels without PVAT in control (p<0.001—multiple ANOVA) and DR (p=0.001—multiple ANOVA) groups. In DIO, the dose–response curves for vessels with intact PVAT and without PVAT were not significantly different (p=0.210—multiple ANOVA). Conclusion: The anticontractile function of PVAT was preserved in DR, but partially lost in DIO. This suggests that weight gain rather than diet itself initiates PVAT damage, which is associated with hypertension. This is the first animal model of environmental obesity in which PVAT function has been studied.